2003
DOI: 10.1377/hlthaff.w3.227
|View full text |Cite
|
Sign up to set email alerts
|

Use Of Subsidies To Low-Income People For Coverage Through Small Employers

Abstract: A proposal to extend employment-based options under publicly funded coverage expansions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Targeting health insurance subsidies to small firms employing low-income workers has been proposed as one means for reducing the number of uninsured [8], a policy that has been receiving increased attention in the recent financial downturn. However, two recent studies have concluded that employer subsidies actually are an inefficient mechanism for increasing insurance coverage [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting health insurance subsidies to small firms employing low-income workers has been proposed as one means for reducing the number of uninsured [8], a policy that has been receiving increased attention in the recent financial downturn. However, two recent studies have concluded that employer subsidies actually are an inefficient mechanism for increasing insurance coverage [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Health insurance offer rates have consistently been shown to decline with firm size [7]. One solution is to couple premium assistance programs for workers with some form of subsidy for their employers as well, particularly to target subsidies to small firms and their low-income employees [8].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of state reform efforts highlight the important role that subsidies can play in boosting take-up, particularly among small employers with low-wage workforces, that is, those most at risk for not offering coverage (Long and Marquis 2001a;Neuschler and Curtis 2003;SilowCarroll, Waldman, and Meyer 2001 Thorpe et al 1992). This suggests that with a maximum subsidy of just 35 percent, the ACA's small business tax credit could have limited impact on spurring increased take-up on the part of employers.…”
Section: Subsidiesmentioning
confidence: 99%
“…Also, there will likely by more turnover by direct support workers if doing so does not result in the loss of their health benefits. Neuschler and Curtis (2003) have suggested that as an alternative to shore up rather than undermine the employment-based system, states should consider crafting a premium subsidy program via the Health Insurance Premium Payment (HIPP) program and/or the Health Insurance Flexibility and Accountability demonstration (HIFA). Many direct support workers who are eligible for publicly subsidized health insurance do participate in employer-provided health plans.…”
Section: Shifting Costs To Public Insurance Versus Supporting Employementioning
confidence: 99%
“…In addition, with federal approval, through the HIFA demonstration initiative, states can also use Medicaid funds to subsidize the purchase of health insurance for ''expansion populations'' that do not satisfy existing Medicaid requirements. Instead of facilitating their enrollment in public programs by providing incentives to ''opt-out,'' these approaches seek to access additional federal dollars and build upon the advantages of a job-based system (Mitchell & Osber, 2002;Neuschler &Curtis, 2003;Sachs, 2003).…”
Section: Shifting Costs To Public Insurance Versus Supporting Employementioning
confidence: 99%